Atmospheric condensation nuclei formation and high-energy radiation - Harrison, R; Aplin, K (2001)
Considerable controversy exists over a proposed link between cosmic radiation and clouds in the apparent absence of a microphysical mechanism between ionisation and particle formation. New atmospheric experimental data which supports previous laboratory evidence of radiolytic particle formation is presented, showing increases in surface condensation nuclei (CN) which correlate positively with increases in surface ionisation. Correlations between physically-displaced Geiger counters are used to attribute some of the ionisation events to cosmic radiation, above a background noise level determined by Monte Carlo simulations of the detector system. When cosmic ionisation events are more frequent, ionisation maxima are followed by increases and then decreases in CN concentration. Some of the variability in atmospheric CN may therefore be attributable to processes initiated by cosmic ionisation. © 2001 Elsevier Science Ltd. All rights reserved.